Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the average rate of change of the function [tex]\( f(x) = -2x^3 + 4x^2 \)[/tex] from [tex]\( x = -1 \)[/tex] to [tex]\( x = 3 \)[/tex], we will follow these steps:
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = -2(-1)^3 + 4(-1)^2 \][/tex]
[tex]\[ f(-1) = -2(-1) + 4(1) \][/tex]
[tex]\[ f(-1) = 2 + 4 = 6 \][/tex]
2. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = -2(3)^3 + 4(3)^2 \][/tex]
[tex]\[ f(3) = -2(27) + 4(9) \][/tex]
[tex]\[ f(3) = -54 + 36 = -18 \][/tex]
3. Calculate the average rate of change using the formula:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
Here, [tex]\( x_1 = -1 \)[/tex] and [tex]\( x_2 = 3 \)[/tex], so:
[tex]\[ \text{Average rate of change} = \frac{f(3) - f(-1)}{3 - (-1)} \][/tex]
Substituting the values we computed:
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 - (-1)} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 + 1} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-24}{4} \][/tex]
[tex]\[ \text{Average rate of change} = -6 \][/tex]
So, the average rate of change of [tex]\( f(x) = -2x^3 + 4x^2 \)[/tex] from [tex]\( x = -1 \)[/tex] to [tex]\( x = 3 \)[/tex] is [tex]\(-6\)[/tex].
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = -2(-1)^3 + 4(-1)^2 \][/tex]
[tex]\[ f(-1) = -2(-1) + 4(1) \][/tex]
[tex]\[ f(-1) = 2 + 4 = 6 \][/tex]
2. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = -2(3)^3 + 4(3)^2 \][/tex]
[tex]\[ f(3) = -2(27) + 4(9) \][/tex]
[tex]\[ f(3) = -54 + 36 = -18 \][/tex]
3. Calculate the average rate of change using the formula:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
Here, [tex]\( x_1 = -1 \)[/tex] and [tex]\( x_2 = 3 \)[/tex], so:
[tex]\[ \text{Average rate of change} = \frac{f(3) - f(-1)}{3 - (-1)} \][/tex]
Substituting the values we computed:
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 - (-1)} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 + 1} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-24}{4} \][/tex]
[tex]\[ \text{Average rate of change} = -6 \][/tex]
So, the average rate of change of [tex]\( f(x) = -2x^3 + 4x^2 \)[/tex] from [tex]\( x = -1 \)[/tex] to [tex]\( x = 3 \)[/tex] is [tex]\(-6\)[/tex].
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.